Marie Unna Hereditary Hypotrichosis: A Turkish Family With Loss of Eyebrows and a U2HR Mutation - ELÇİOĞLU, HURİYE NURSEL; ÇETİNEL, ŞULE (WILEY-LISS, 2010)
We report a family with Marie Unna hereditary hypotrichosis (MUHH) from Turkey. MUHH is a distinct form of scalp and body hair loss characterized by the absence or scarcity of scalp hair, eyebrows, and eyelashes at birth. Coarse wiry hair begins to grow during childhood. Around puberty, progressive hair loss occurs in the affected patients. Recently, mutations were identified in U2HR, an inhibitory upstream open reading frame in the 5'-untranslated region of the human hairless gene (HR) as the underlying cause of MUHH. We are presenting hair loss of eyebrows in a Turkish family comprising eight affected and seven unaffected individuals. The pedigree is compatible with autosomal dominant inheritance. Linkage and haplotype analyses confirmed linkage of this family to the MUHH locus at cytoband 8p21. By sequencing U2HR, we identified the mutation c.2T > C (M1T) in all affected family members. We concluded that there may be considerable clinical variations in MUHH, and that eyebrow loss is an important clue for accurate diagnosis. (C) 2010 Wiley-Liss, Inc.
Keywords: congenital hypotrichosis; eyebrows; Marie Unna hereditary hypotrichosis; U2HR mutation; CHINESE FAMILY; GENE; MAPS; HAIRLESS; SIMPLEX